DIGITAL VULNERABILITY AND THE ABSENT STATE: THE POLITICS OF DATA PRIVACY IN SOMALIA’S UNREGULATED DIGITAL ECONOMY - Osman, Abdullahi Ilyas; Jarras, Aweis Ahmed Hussein (Veredas do Direito, 2026)
Somalia’s rapidly expanding digital economy driven by telecommunications, mobile money (notably EVC Plus, Zaad, and e-Dahab), and online platforms has outpaced institutional development, creating heightened exposure to privacy violations, surveillance, and data misuse in a context of weak state capacity since 1991. This study examined how regulatory absence produces digital vulnerability, how the politics of depoliticized data privacy shifts governance to private providers, and how these dynamics affect citizens’ rights and trust in digital systems. Guided by theories of state failure, governance in fragile states, political economy of technology, surveillance capitalism, and institutional theory, the research employed a quantitative descriptive–explanatory design. A simple random sample of 353 adult digital-service users from Mogadishu, Hargeisa, and Kismayo was surveyed via a structured Kobo Toolbox questionnaire; 328 valid responses (92.9%) were analyzed in SPSS 31 using reliability tests, descriptive statistics, Pearson correlations, and multiple linear regression (p<0.05). Respondents reported high digital vulnerability (M=4.12/5), very high perceived state absence in digital governance (M=4.38/5), and strong perceptions of depoliticized privacy dominated by corporate discretion (M=4.05/5); scales showed strong internal consistency (overall α=0.901). Digital vulnerability correlated strongly with state absence (r=0.67) and politics of data privacy (r=0.71), while vulnerability was associated with reduced trust (r=-0.62). Regression results indicated that state absence and politics of data privacy explained 57% of variance in vulnerability (adjusted R²=0.57), with private-sector dominance the stronger predictor (β=0.49) relative to state absence (β=0.30). Findings show that Somalia’s digital insecurity is structural and governance-driven rather than technical, characterized by financial surveillance (DV2–DV5 r=0.59), lack of legal recourse, and coerced reliance on unregulated systems. Strengthening data protection law, enforcement institutions, accountability mechanisms, and citizen redress is therefore central to safeguarding rights and sustaining trust in Somalia’s digital economy.